Evaluation of healthcare professionals' understanding of eponymous maneuvers and mnemonics in emergency obstetric care provision1. Issue 3 (11th March 2014) - Jan, Haider; Guimicheva, Boriana; Gosh, Srirupa; Hamid, Rosol; Penna, Leonie; Sarris, Ippokratis
Abstract: Objective: To evaluate whether eponymous maneuvers and mnemonics taught for the management of shoulder dystocia, vaginal breech delivery, and uterine inversion were remembered and understood in practice. Methods: A questionnaire was distributed to obstetricians and midwives collecting information about the HELPERR and PALE SISTER mnemonics. Three extended matching questions evaluated participants' knowledge of the correct maneuvers, with their matching eponyms, used in the management of shoulder dystocia, vaginal breech delivery, and uterine inversion. Results: Of the 112 participants, 90% were familiar with the HELPERR mnemonic, with 79% using it in their practice. Of those who used it, only 32% could correctly decipher it ( P = 0.032). PALE SISTER was mostly unfamiliar. The percentages of correct maneuvers used for managing shoulder dystocia, breech delivery, and uterine inversion were 84.6%, 58.3%, and 28.6%, respectively. However, the eponyms were correctly matched to their maneuvers in only 33.3%, 14.3%, and 0% of cases, respectively ( P < 0.01). Conclusion: The meanings of the mnemonics for obstetric emergencies were frequently recalled incorrectly. This, together with the poor correlation between knowledge of maneuvers and their eponyms, limits their usefulness and indicates that teaching should focus on learning without relying on mnemonics and eponyms.